Comparison of oropharyngeal leak pressure between the SaCoVLM™ video laryngeal mask and LMA supreme in adult elective surgery patients: a prospective randomized controlled trial - Gaye Gamze Ozden; Burhan Dost; Cengiz Kaya; Esra Turunc; Ersin Koksal; Yasemin Burcu Ustun; Sezgin Bilgin; Sibel Baris (BMC Anesthesiology)
Abstract Background This study aimed to compare the oropharyngeal leak pressure (OLP) of SaCoVLM™ with that of LMA Supreme. Methods This prospective, randomized, controlled, single-blind study enrolled patients aged 18–80 years with American Society of Anesthesiologists physical status of classes I and II. The OLP was the primary outcome measure of the study. The glottic visualization grades, laryngeal mask insertion time and number of attempts, requirement for additional maneuvers, and incidence of complications were the secondary outcome measures. Results A total of 168 patients, comprising 83 patients in the SaCoVLM™ group and 85 patients in the LMA Supreme group, were included in this study. The median OLP values were 27 [24.0–30.0] cmH2O and 25 [20.0–35.0] cmH2O in the SaCoVLM™ and LMA Supreme groups, respectively. No significant differences were observed between the groups in terms of the OLP (p > 0.05). The first-attempt success rate in the SaCoVLM™ group was significantly higher than that in the LMA supreme group (98.8% vs. 91.8%, p = 0.034). In terms of glottic assessment, the complete glotis visualization rate in the SaCoVLM™ group (p < 0.001) was significantly higher than that in the LMA supreme group. However, the Grade 1–3 visualization rates were significantly lower in the SaCoVLM™ group (p < 0.001). Complications such as mucosal damage and postoperative sore throat were observed more frequently in the LMA Supreme group (p = 0.001). Conclusions SaCoVLM™, which offers comparable OLP, superior glottic visualization, high first-attempt success rates, and a lower incidence of complications, may serve as an alternative supraglottic airway device. Trial registration The study was registered on ClinicalTrials.gov (Identifier: NCT06245668).